Cardiac Magnetic Resonance Imaging used for Evaluation of Adipose-Derived Stromal Cell Therapy in Patients with Chronic Ischemic Heart Disease. Issue 12 (December 2019) - Qayyum, Abbas Ali; Mathiasen, Anders Bruun; Mygind, Naja Dam; Vejlstrup, Niels Groove; Kastrup, Jens
Adipose-derived stromal cell (ASC) therapy is currently investigated as a new treatment option for patients with ischemic heart disease (IHD). The aim of this study was to evaluate the effect of ASC therapy in patients with chronic IHD measuring myocardial perfusion and cardiac function using cardiac magnetic resonance imaging (CMRI). Patients were included in MyStromalCell trial, a phase II, randomized, double-blinded, placebo-controlled study investigated the effect of ASCs in patients with chronic IHD with preserved left ventricular ejection fraction (LVEF). In total, 41 of 60 patients underwent cine, late enhancement, rest and stress imaging with CMRI. There was a non-significant difference between stress and rest values in maximal signal intensity, a measure of myocardial perfusion, from baseline to follow-up comparing placebo with ASC group (–52.52 ± 88.61 and 3.05 ± 63.17, p = 0.061, respectively). LVEF, myocardial mass, stroke volume, left ventricle end-diastolic volume and end-systolic volume changed non-significantly (–0.5 ± 4.7%, –3.5 ± 13.1 g, –0.7 ± 8.6 mL, 1.9 ± 25.1 mL and 2.6 ± 16.5 mL, respectively) in the placebo group and in the ASC group (0.7 ± 8.6%, 0.9 ± 10.8 g, –0.3 ± 26.1 mL, –3.0 ± 31.5 mL and –2.7 ± 20.4 mL, respectively) from baseline to 6 months follow-up. The amount of scar tissue was unchanged in the placebo group by 0.0 ± 1.6 g, p = 1.0 and in the ASC group with –0.3 ± 2.3 g, p = 0.540. There was no difference between the groups. There was a non-significant trend toward increased myocardial perfusion but no significant changes in functional parameters or amount of scar tissue in patients treated with ASCs compared with patients allocated into the placebo group.